Molecular insights into substrate specificity of prostate specific antigen through structural modeling. - Singh, P; LeBeau, A; Lilja, H; Denmeade, SR; Isaacs, J (2009)
Prostate Specific Antigen's (PSA) role as a biomarker for prostate cancer is well established but the physiological role of its serine protease activity in the pathobiology of normal prostate and prostate carcinogenesis remains largely unknown. In light of recent studies that implicate PSA's enzymatic activity in the initiation and/or progression of prostate cancer, we performed a molecular modeling study of substrate binding at the catalytic site of PSA wherein a PSA-selective substrate (HSSKLQ) was docked in an acyl-enzyme conformation to a three-dimensional homology model of PSA. Additionally, virtual positional scanning studies were conducted to gain mechanistic insights into substrate recognition of PSA. Subsequently, 13 novel peptide substrates of 6-aa length and four peptide substrates with varying length were synthesized and assayed for PSA hydrolysis to evaluate the experimental validity of docking insights. Additionally, six novel aldehyde-containing transition state analog inhibitors were synthesized and tested for their inhibitory potencies. The experimental data on the hydrolysis rates of the newly synthesized substrates and inhibitory potencies of the aldehyde peptides agreed with the docking predictions, providing validation of the docking methodology and demonstrating its utility towards the design of substrate-mimetic inhibitors that can be used to explore PSA's role in the pathobiology of prostate cancer.